La utilización del método Montessori para potenciar el razonamiento lógico- matemático de las niñas y niños de 4 a 5 años de edad, en el Centro de Desarrollo Infantil Abendaño Children’s School de la Ciudad de Loja. Período 2014-2015 - Ruíz Jadán, Ximena Soledad (2016)
In this research work, entitled The use of the Montessori method for enhancing the logical-mathematical reasoning of children from 4-5 years of age in the Child Development Center Abendaño Children's School in the city of Loja. 2014-2015. Which constitutes an important contribution to the overall education of children, for which the overall objective was formulated: To analyze the use of the Montessori method for enhancing the logical-mathematical reasoning of children from 4-5 years of age in Child Development Center Abendaño Children's School of the City of Loja. Period 2014-2015, the methods used were scientific, descriptive, deductive-inductive, analytic Systematic and Statistical method; the techniques used during the research were applied interview that the 2 teachers of the institution and the sheet perform observation that the 25 children from the Child Development Center. There is 100% of the teachers know that if they use and the use of the Montessori method, since the teachers 'guide' to respect and know each child and help in the development of learning and 92% of the and the children develop their mathematical logical reasoning mediantes activities undertaken